Training of Academic Writing for Senior High School English Teachers: Formulating Research Questions - Adaninggar Septi Subekti (Universitas PGRI Semarang, 2020)
This article reports a community service activity conducted to give training to Senior High School English teachers in Bantul Regency, Yogyakarta, Indonesia, on academic writing, especially on formulating research questions of their Classroom Action Research (CAR). The training was a part of series of training conducted by the lecturers of the English Language Education Department of Universitas Kristen Duta Wacana (UKDW) at regular Senior High School Teacher Professional Development Forum (MGMP) meetings. It was conducted to answer the teachers’ needs to conduct educational research for their professional development and career advancement as regulated by the government. The training on formulating research questions in CAR was divided into two sessions. The first session was lecture session in which relevant theories, practical suggestions, and examples regarding research questions were presented to the participants. This session, despite resource-person-led, could be interrupted with immediate questions from the teacher participants, allowing a more dynamic discussion. The second session was workshop session in which the participants practiced formulating research questions based on their respective teaching contexts with a close guidance from the resource person. Based on a reflective evaluation on the training, several conclusions on what had gone well and what needed to be improved are also presented along with several suggestions regarding possible follow-up trainings in the future.